Hybrid Model In Machine Learning With Robust Regression For Handling Multicollinearity Outlier In Big Data And Its Application To Agriculture - ., Mukhtar (2023)
In this research, 29 independent single variables and 435 independent interaction variables were identified. The limitation of this research were to address the problems such as irrelevant variables, multicollinearity and outliers.